IDENTIFIKASI RONGGA MENGGUNAKAN METODE GEOLISTRIK KONFIGURASI DIPOLE-DIPOLE DAERAH NUSAKAMBANGAN CILACAP JAWA TENGAH - Andi; Ajimas Pascaning Setiahadiwibowo (KURVATEK, 2020)
The identification of cavities on Nusakambangan island using the geoelectrical resistivity method of dipole-dipole configuration has been carried out. This method was used for lateral resistivity mapping on each path. The geoelectric resistivity test was performed by four paths with a length of 200 - 400 m. The results showed that there were several closure patterns that were interpreted as cavities along the surveyed trajectory. The closure patterns are (i) three on path A with a resistivity of more than 4000 ohmmeters, (ii) two on path B with a resistivity of more than 10000 ohmmeters, (iii) one on path C with a resistivity of more than 10000 ohmmeters, and (iv) two on path D with a resistivity of more than 2000 ohmmeter. Our results could be used as an illustration to mark locations on the surface where the sinkhole potential of a disaster exists.Keywords: Cavity; Dipole-dipole; Geoelectric; Resistivity